Cognitive Impairment after Severe Traumatic Brain Injury, Clinical Course and Impact on Outcome: A Swedish-Icelandic Study - Maud Stenberg; Alison K. Godbolt; Catharina Nygren De Boussard; Richard Levi; Britt-Marie Stålnacke (Behavioural Neurology)
Objective. To assess the clinical course of cognitive and emotional impairments in patients with severe TBI (sTBI) from 3 weeks to 1 year after trauma and to study associations with outcomes at 1 year. Methods. Prospective, multicenter, observational study of sTBI in Sweden and Iceland. Patients aged 18–65 years with acute Glasgow Coma Scale 3–8 were assessed with the Barrow Neurological Institute Screen for Higher Cerebral Functions (BNIS) and the Hospital Anxiety and Depression Scale (HADS). Outcome measures were Glasgow Outcome Scale Extended (GOSE) and Rancho Los Amigos Cognitive Scale-Revised (RLAS-R). Results. Cognition was assessed with the BNIS assessed for 42 patients out of 100 at 3 weeks, 75 patients at 3 months, and 78 patients at 1 year. Cognition improved over time, especially from 3 weeks to 3 months. The BNIS subscales “orientation” and “visuospatial and visual problem solving” were associated with the GOSE and RLAS-R at 1 year. Conclusion. Cognition seemed to improve over time after sTBI and appeared to be rather stable from 3 months to 1 year. Since cognitive function was associated with outcomes, these results indicate that early screening of cognitive function could be of importance for rehabilitation planning in a clinical setting.